In‐vitro analysis of a novel 'add‐on' silicone cuff to improve sealing properties of tracheal tubes. (8th October 2018) - Li Bassi, G.; Chiurazzi, C.; Aguilera, E.; Travierso, C.; Battaglini, D.; Yang, M.; Motos, A.; Yang, H.; Meli, A.; Marti, D.; Ranzani, O. T.; Blasi, F.; et al.
Summary: Leakage of colonised oropharyngeal secretions across the tracheal tube cuff may cause iatrogenic pulmonary infection. We studied a novel 'add‐on' cuff, which can be inserted over an existing tracheal tube and advanced into the subglottic region. The physical properties of the novel silicone cuff (BronchoGuard, Ciel Medical, USA) were evaluated in comparison with the Hi‐Lo ® tracheal tube. In a bench study, we identified saline inflation volumes required to transmit pressures between 15 and 30 cmH2 O against artificial tracheas of 18, 20 and 22 mm internal diameter. We computed cuff compliance, and minimal inflation volume to achieve air sealing during mechanical ventilation. Finally, we compared the leakage flow rate of artificial saliva across the novel cuff. On average, the mean (SD) inflation volumes necessary to transmit tracheal pressures of 15, 20, 25 and 30 cmH2 O were 4.1 (2.2), 4.4 (2.3), 4.6 (2.4) and 4.8 (2.4) ml for the novel cuff and 7.7 (2.5), 8.0 (2.6), 8.4 (2.6) and 8.7 (2.7) ml for the Hi‐Lo tube, respectively (p < 0.001). The minimal inflation volumes to achieve air sealing were 3.8 (0.9) and 10.5 (2.1) ml (p < 0.001), which resulted in transmitted tracheal pressures of 8.3 (9.8) and 27.6 (34.8) cmH2 O (p < 0.001). Compliance was 0.026 (0.004) and 0.616 (0.324) ml.cmH2 0 −1, respectively (p < 0.001). Although massive leak was found when the novel cuff transmitted pressures ≤ 20 cmH2 O against the trachea, leakage was avoided with pressures ≥ 25 cmH2 O, owing to optimal contact between the cuff and the tracheal wall. In contrast, the standard cuff consistently leaked irrespective of the pressure. We conclude that the novel cuff has advantageous properties that warrant clinical corroboration.